ВПЛИВ ВПРОВАДЖЕННЯ ТЕХНОЛОГІЙ ІНДУСТРІЇ 4.0 НА РЕАЛІЗАЦІЮ МІЖНАРОДНИХ КОНКУРЕНТНИХ СТРАТЕГІЙ НАЦІОНАЛЬНИХ ЕКОНОМІК - Popko, Olena; Verbovskyi, Igor (Zhytomyr Ivan Franko State University, 2023)
Modern technological transformations associated with Industry 4.0 have a significant influence on the competitiveness of national economies on a global scale. The article analyzes the impact of the introduction of Industry 4.0 technologies on the implementation of international competitive strategies, focusing on key economies such as China, the United States of America, Germany, France, Japan, South Korea, India, Australia, Brazil, South Africa, Pakistan, Venezuela, and Ukraine. The main competitive strategies that take into account the new technological context are considered. These include digital transformation strategies, the use of artificial intelligence, the Internet of Things and other aspects of Industry 4.0. In particular, the article examines which technological innovations are reflected in the strategies of leading countries and how they contribute to their international competitive success. Great attention is paid to the aspects that influence the formation of competitive strategies of national economies, such as changes in global supply chains, development of digital platforms, cybersecurity and response to the challenges of technological shifts. The main focus is on the fact that enterprises tending to increase their international competitiveness should develop strategies taking into account the new technological context. The core strategies are digital transformation, globalization, innovation, and partnership. These strategies include adjusting to new technologies, increasing international presence, seeking innovation, and cooperating with other parties for common success. The paper highlights not only the positive aspects of implementing Industry 4.0 technologies, but also the risks associated with the unequal distribution of technological capabilities between countries. It emphises the interaction of countries in the context of international economic relations and the development of cooperation strategies to ensure mutual benefits. The article can serve as an important source for specialists in the field of economics, public administration and business, as well as for researchers interested in the relationship between technological development and the competitiveness of national economies in the modern world.